The Impacts of Seawater Mg/Ca and Temperature on Element Incorporation in Benthic Foraminiferal Calcite. (20th October 2017) - de Nooijer, L. J.; van Dijk, I.; Toyofuku, T.; Reichart, G. J.
Abstract: On geological timescales, oceanic [Mg 2+ ] and [Ca 2+ ] vary with changing rates of weathering, seafloor spreading and dolomite formation. Accurate reconstruction of the ratio between [Mg 2+ ] and [Ca 2+ ] in seawater (Mg/Casw ), may potentially be reconstructed using foraminiferal Mg/Ca ratios. Since both temperature and seawater Mg/Ca impact foraminiferal Mg/Ca, successful reconstruction of Mg/Casw requires quantification of both these parameters independently on foraminiferal Mg/Ca, as well as their combined effect on Mg‐incorporation. Here we present the combined and isolated impacts of temperature and Mg/Casw on Mg incorporation in two model species, the benthic hyaline (i.e., perforate) foraminifer Elphidium crispum and porcelaneous (i.e., miliolid) foraminifer Quinqueloculina sp. using controlled growth experiments. Specimens of these two species were kept at four different temperatures (ranging from 10 to 27°C) and three Mg/Casw 's (3.4, 6.4 and 8.5 mol/mol), resulting in 12 experimental conditions. Newly grown calcite was analyzed for a number of elements (Na, Mg and Sr) by laser ablation‐ICP‐MS. Results show that although the Mg/Ca varied by more than an order of magnitude between species, the sensitivity of Mg incorporation with respect to temperature appeared not to be influenced by Mg/Casw . By extension, these results may also help improving accuracy in the reconstruction of past Mg/Casw based on foraminifera with contrasting Mg/Ca. Key Points: Two foraminiferal species were cultured at a range of temperatures and seawater Mg/Ca These parameters appeared to influence element incorporation independently General differences between these two species are caused by differences in their biomineralization pathways